2019
DOI: 10.3390/ijms20040904
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resveratrol in Patients with Cardiovascular Disease and Heart Failure: A Narrative Review

Abstract: Cardiovascular disease (CVD) is the main cause of death globally and responsible for the second highest number of deaths in Canada. Medical advancements in the treatment of CVD have led to patients living longer with CVD but often progressing to another condition called heart failure (HF). As a result, HF has emerged in the last decade as a major medical concern. Fortunately, various “traditional” pharmacotherapies for HF exist and have shown success in reducing HF-associated mortality. However, to augment the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 148 publications
(230 reference statements)
1
85
0
8
Order By: Relevance
“…Decreased apoptosis and increased autophagy Rat H9c2 cardiomyoblasts [94] questionable. However, resveratrol has been implicated as a cardioprotective drug for many cardiovascular diseases both in preclinical studies [121] and in man [122], and this is thought to be largely due to its anti-inflammatory and anti-oxidant action [123]. Of specific interest for the topic of this review, resveratrol has been shown to lead to activation of AMPK and to reduce cardiac fibrosis and hypertrophy in a mouse model of pressure overload by transverse aortic constriction [124].…”
Section: Resveratrolmentioning
confidence: 99%
“…Decreased apoptosis and increased autophagy Rat H9c2 cardiomyoblasts [94] questionable. However, resveratrol has been implicated as a cardioprotective drug for many cardiovascular diseases both in preclinical studies [121] and in man [122], and this is thought to be largely due to its anti-inflammatory and anti-oxidant action [123]. Of specific interest for the topic of this review, resveratrol has been shown to lead to activation of AMPK and to reduce cardiac fibrosis and hypertrophy in a mouse model of pressure overload by transverse aortic constriction [124].…”
Section: Resveratrolmentioning
confidence: 99%
“…RSV has gained much interest due to its potential to generate a range of therapeutic effects and the suggestion that it is a contributing factor in the so-called "French paradox": the observed reduced risk of coronary artery disease in French people attributed at least in part to the regular consumption of red wine [2]. There is good evidence for RSV supporting the heart function, protecting against cardiovascular diseases [3], neuro-disorders [4,5], diabetes [6], and cancer [7], due to its antioxidant and anti-inflammatory effects. Of particular relevance to this article, RSV has demonstrated a potential for antiaging effects and for protecting against UV damage in the skin due to its antioxidant and collagen stimulating activity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The first identified SIRT1 activator was resveratrol, currently used in the treatment of various diseases [19][20][21][22][23][24]. Recent efforts have focused on discovering new synthetic SIRT1-activating compounds (STACs) [25,26].…”
Section: Introductionmentioning
confidence: 99%